Contribuições para o avanço da Economia da Saúde no Sistema de Saúde Brasileiro - Macêdo, Everton; Castro, Marcelo; Silva, Maciene; Trigueiro, Wesley (Jornal Brasileiro de Economia da Saúde, 2022)
Artigo Institucional